Enjeux du jeu de mots : Perspectives linguistiques et littéraires - Winter-Froemel, Esme; Zirker, Angelika (Dynamics of wordplay, 2015)
In conjunction with the first volume of the series, this collection of essays analyzes techniques and basic traditions of wordplay in various communicative situations and offers new perspectives on the dynamics of wordplay as an interface phenomenon.